Corporate Social Performance on Cost of Equity, Cost of Debt with Institutional Ownership, And Bank Dependency as Moderating Variables - Salim, Noor; Sugiharti, Sugiharti; Bhandari, Rahul; Nasir, Wan Mohd Nazdrol bin Wan Mohd; Thongkamkaew, Chanwut; Permatasari, Novita (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2022)
This research aims to analyze corporate social performance on the cost of equity, cost of debt with institutional ownership, and bank dependency as moderating variables The population of this research is non-financial companies listed on the Indonesian Stock Exchange (IDX), Bombay Stock Exchange (BSE), Malaysia stock exchange (MYX) and e Stock Exchange of Thailand (SET) from 2016-2020. The sample was selected using purposive sampling and 95 companies were obtained as research samples. The type of data used is secondary data. The data used was obtained from the company's annual report. The analysis techniques used in this research are moderating regression analysis and multiple regression analysis. The results of this study indicate that disclosure of corporate social performance does not have a significant effect on the cost of equity. Institutional Ownership moderates the positive and significant relationship between corporate social performance and the cost of equity. bank dependency does not moderate the effect of corporate social performance on the cost of equity. Corporate social performance has a negative and significant effect on the cost of debt. institutional ownership moderates the negative and significant relationship between corporate social performance and the cost of debt. Bank dependency moderates the positive and significant relationship between corporate social performance and the cost of debt.